Proposed Model of the Relationship Between Problem-Solving Skills and Aggression Mediated by Emotional Intelligence in Male Secondary School Students - Fathi, Farrokhlagha; Karimi Baghmalek, Ayatollah (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The aim of this study was to investigate the relationship between problem-solving skills and aggression among male secondary school students, with emotional intelligence acting as a mediating variable. Methods and Materials: This descriptive, correlational study employed a path analysis design. The statistical population included all male secondary school students in Ahvaz, Iran, from which 200 participants were selected using multistage random sampling. Data were collected through three standardized instruments: the Problem Solving Inventory (PSI), the Aggression Questionnaire (AQ), and the Wong and Law Emotional Intelligence Scale (WLEIS). Data analysis was conducted using Pearson correlation coefficients and path analysis via SPSS-23 and AMOS-22 software. Findings: The results showed significant negative correlations between all dimensions of problem-solving skills and aggression: problem-solving confidence (r = -0.413, p < .01), approach-avoidance style (r = -0.486, p < .01), personal control (r = -0.418, p < .01), and the total problem-solving score (r = -0.630, p < .01). Emotional intelligence also demonstrated a strong negative correlation with aggression (r = -0.702, p < .01). Path analysis revealed that emotional intelligence significantly mediated the relationship between each problem-solving component and aggression. The strongest standardized path coefficient was observed between emotional intelligence and aggression (β = -0.535, p < .01). Fit indices confirmed the acceptability of the model (CFI = 0.99, TLI = 0.90, NFI = 0.98), despite a slightly elevated RMSEA (0.116). Conclusion: The findings suggest that both problem-solving skills and emotional intelligence play significant roles in reducing aggressive behaviors among adolescents. Emotional intelligence serves as a key mediating factor, reinforcing the importance of integrating cognitive and emotional skill development in school-based interventions aimed at aggression prevention.